1994
DOI: 10.1161/01.res.75.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ablation of the phospholamban gene is associated with markedly enhanced myocardial contractility and loss of beta-agonist stimulation.

Abstract: Phospholamban is the regulator of the Ca'+-ATPase in cardiac sarcoplasmic reticulum (SR), and it has been suggested to be an important determinant in the inotropic responses of the heart to 8-adrenergic stimulation. To determine the role of phospholamban in vivo, the gene coding for this protein was targeted in murine embryonic stem cells, and mice deficient in phospholamban were generated. The phospholamban-deficient mice showed no gross developmental abnormalities but exhibited enhanced myocardial performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
515
0
5

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(559 citation statements)
references
References 46 publications
39
515
0
5
Order By: Relevance
“…13) without activating receptor-mediated pathways (e. g., β-adrenergic receptors) could be promising. In experimental heart failure models, transgenic inhibition or deletion of phospholamban [51, 116,134] or adenoviral increase of SR Ca 2+ -ATPase expression [52] frequently, but not always [185], improved LV function and survival. Interestingly, the increase of SR Ca 2+ -ATPase expression was associated with an improvement of the PCr/ATP ratio in rats with heart failure after aortic banding [52], supporting the hypothesis that reconstitution of EC coupling may improve energetics.…”
Section: Discussionmentioning
confidence: 99%
“…13) without activating receptor-mediated pathways (e. g., β-adrenergic receptors) could be promising. In experimental heart failure models, transgenic inhibition or deletion of phospholamban [51, 116,134] or adenoviral increase of SR Ca 2+ -ATPase expression [52] frequently, but not always [185], improved LV function and survival. Interestingly, the increase of SR Ca 2+ -ATPase expression was associated with an improvement of the PCr/ATP ratio in rats with heart failure after aortic banding [52], supporting the hypothesis that reconstitution of EC coupling may improve energetics.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that absence of PLB enhanced SR calcium uptake and increased rates of contraction and relaxation. This was associated with an increase in SERCA2a affinity for calcium [41]. On the other hand, over-expression of PLB in the heart resulted in a decrease in SR Ca 2+ uptake and depressed cardiac contractile performance in vivo.…”
Section: Transgenic Approaches To Study the Role Of Plb And Sln In Camentioning
confidence: 97%
“…Studies using genetically altered mouse models have given important insight into the role of PLB in cardiac physiology. Using a PLB knockout mouse model [41], Dr. Kranias and colleagues provided the crucial evidence that PLB is an important regulator of the SERCA2a. They showed that absence of PLB enhanced SR calcium uptake and increased rates of contraction and relaxation.…”
Section: Transgenic Approaches To Study the Role Of Plb And Sln In Camentioning
confidence: 99%
“…Increased contractility [170] Preserves cardiac contractility and left ventricular chamber size close to normal in MLP-deficient mice [193] Restoring expression of S100A1 to normal levels in post-MI rats improved LV function and reduced LV dilation S100A1 [229] Overexpression…”
Section: General Considerationsmentioning
confidence: 99%